Dismantling the signposts to public health? NHS data under the Health and Social Care Act 2012. (26th April 2012) - Pollock, Allyson M; Macfarlane, Alison; Godden, Sylvia
Abstract : A shift away from area based populations in England will have severe implications for population health data, argue Allyson M Pollock, Alison Macfarlane, and Sylvia Godden